2007
DOI: 10.1002/ijc.23097
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin enhances the effects of 5‐fluorouracil and oxaliplatin in mediating growth inhibition of colon cancer cells by modulating EGFR and IGF‐1R

Abstract: Curcumin (diferuloylmethane), which has been shown to inhibit growth of transformed cells, has no discernible toxicity and achieves high levels in colonic mucosa. 5-fluorouracil (5-FU) or 5-FU plus oxaliplatin (FOLFOX) remains the backbone of colorectal cancer chemotherapeutics, but with limited success. The present investigation was, therefore, undertaken to examine whether curcumin in combination with conventional chemotherapeutic agent(s)/regimen will be a superior therapeutic strategy for colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
133
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 35 publications
9
133
0
2
Order By: Relevance
“…In a larger cohort of patients with breast cancer treated with doseintensified adjuvant anthracycline and taxane therapy, IGF-I and IGFBP-3 levels increased significantly during therapy (Kummel et al 2007). This last observation is supported by in vitro data showing that genotoxic drugs can increase IGFBP-3 protein levels in tumor cell lines (Zadeh & Binoux 1997, Grimberg et al 2005, Patel et al 2008). As described above, a significant decrease in IGFBP-3 was observed in our study at disease progression, compared with basal and treatment levels.…”
Section: Discussionmentioning
confidence: 59%
“…In a larger cohort of patients with breast cancer treated with doseintensified adjuvant anthracycline and taxane therapy, IGF-I and IGFBP-3 levels increased significantly during therapy (Kummel et al 2007). This last observation is supported by in vitro data showing that genotoxic drugs can increase IGFBP-3 protein levels in tumor cell lines (Zadeh & Binoux 1997, Grimberg et al 2005, Patel et al 2008). As described above, a significant decrease in IGFBP-3 was observed in our study at disease progression, compared with basal and treatment levels.…”
Section: Discussionmentioning
confidence: 59%
“…The proliferation of HT29 and HCT15 human colon cancer cell lines was inhibited by curcumin treatment, which arrested the cell cycle in the G2/M phase with no detected apoptosis [135] . Curcumin administered in combination with 5FU plus oxaliplatin resulted in increased inhibition of growth and enhanced apoptosis in HCT116 and HT29 colon cancer cells compared to each of these drugs alone, and these effects were attained mainly through the attenuation of the EGFR and IGF1R signaling pathways [136] . The induction of autophagy activation and ROS production was observed in HCT116 human colon cancer cells that were treated with curcumin, and they showed higher mRNA and protein LC3 levels [137] .…”
Section: Autophagy Drugs In Crcmentioning
confidence: 96%
“…In addition to the effectiveness of curcumin alone, it is being currently evaluated in combination therapy (Koo et al, 2004;Kamat et al, 2007;Kunnumakkara et al, 2007;Lev-Ari et al, 2007;Patel et al, 2008). Kunnumakkara et al (2007) demonstrated that curcumin can potentiate the antitumour effects of gemcitabine by suppressing the proliferation and angiogenesis in an orthotopic model of pancreatic cancer.…”
Section: Chk1 Activation By Curcumin Rp Sahu Et Almentioning
confidence: 99%